(untitled) (Journal of Plant Disease Sciences, 2017)
Trichoderma Phytophthora spp., used for managing soil borne rot in citrus orchards is observed to cause post harvest fruit rots. Therefore, it is imperative to develop management tool for this upcoming threat. Looking at the development of resistance in pathogen against effective fungicides and their environmental hazards, some alternative methods are suggested but they are not as effective as fungicides. Combining them with fungicides will make fungicides efficient at lower doses thus reducing environmental risk. In this experiment fungicide, edible wax and antagonist are used in combination. Among treatments on 15 day Propiconazole th 0.1% + Vegetable Wax 6%, Imazalil 0.1% + Citracine Wax 6% and Imazalil 0.1% + Vegetable Wax 6% were at par. Incremental Cost Benefit Ratio was maximum (1:17.10) for Propiconazole 0.1% + Vegetable Wax 6% followed by Propiconazole 0.1% + Citracine Wax 6% (1:12.07). Pesticide Residue Analysis for Propiconazole by High Power Liquid Chromatography technique showed 20-30 times less residues than Maximum Residue Limit set by Europe, Codex Alimentarius Commission, Canada and USA. It shows that dipping of Nagpur mandarin fruits in 1ml/litre of Propiconazole followed by coating with 6% Vegetable or Citracine Wax protect fruits from Trichoderma rot upto 15 days of harvesting under ambient conditions.